Nanotherapeutics for Meningitis: Enhancing Drug Delivery Across the Blood-Brain Barrier - Hitaishi Sharma; Kannan Badri Narayanan; Shampa Ghosh; Krishna Kumar Singh; Prarthana Rehan; Aparajita Dasgupta Amist; Rakesh Bhaskar; Jitendra Kumar Sinha (Biomimetics)
Meningitis is the acute or chronic inflammation of the protective membranes, surrounding the brain and spinal cord, and this inflammatory process spreads throughout the subarachnoid space. The traditional drug delivery methods pose a disadvantage in limiting the capacity of crossing the blood–brain barrier (BBB) to reach the central nervous system (CNS). Hence, it is imperative to develop novel approaches that can overcome these constraints and offer efficient therapy for meningitis. Nanoparticle (NP)-based therapeutic approaches have the potential to address the limitations such as penetrating the BBB and achieving targeted drug release in specific cells and tissues. This review highlights recent advancements in nanotechnology-based approaches, such as functionalized polymeric nanoparticles, solid lipid nanoparticles (SLNs), nanostructured lipid carriers, nanoemulsions, liposomes, transferosomes, and metallic NPs for the treatment of meningitis. Recently, bionics has emerged as a next-generation technology in the development of novel ideas from biological principles, structures, and interactions for neurological and neuroinfectious diseases. Despite their potential, more studies are needed to ensure the safety and efficacy of NP-based drug delivery systems focusing on critical aspects such as toxicity, immunogenicity, and pharmacokinetics. Therefore, this review addresses current treatment strategies and innovative nanoparticle approaches, and it discusses future directions for efficient and targeted meningitis therapies.